Hydrodynamics of bubble column reactors at high gas velocity: experiments and computational fluid dynamics (CFD) Simulations - Rampure, Mohan R.; Kulkarni, Amol A.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2007)
This paper focuses on the modeling of flow and mixing in a bubble column reactor operated at high gas velocities (up to 0.40 m/s). A dual-tip conductivity probe was used to measure local void properties such as local time-averaged gas holdup, chord length distribution, bubble velocity distribution, and interfacial area. Chord length distribution was converted to bubble size distribution, using the backward transformation method. Liquid-phase mixing time measurements were conducted using a conductivity probe. A computational fluid dynamics (CFD) model was developed to simulate the unsteady gas-liquid flow in a bubble column using commercial code FLUENT 6.2. The time-averaged flow properties predicted by CFD simulations were compared with the experimental data. The role of unsteady flow structures in mixing was studied. The `' multiple snapshots `' approach was used to simulate the mixing time using CFD. The mixing times that were predicted for all superficial gas velocities compared favorably to the measured values. This study of the hydrodynamic behavior of a bubble column at higher gas velocity provides a basis for understanding and simulating solid suspension (or solid mixing) in slurry bubble column reactors.
Joint 6th International Symposium on Catalysis in Multiphase Reactors/5th International Symposium on Multifunctional Reactors (CAMURE-6/ISMR-5-), Pune, INDIA, JAN 14-17, 2007